Upaya Pencegahan Dan Penindakan Transaksi Narkotika Oleh Narapidana Di Lingkungan Lembaga Pemasyarakatan - Anisa, Jenny; Dewi, Erna; Putri, Ria Wierma; Maroni, Maroni; Siswanto, Heni (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The surveillance system in correctional institutions plays an important role in suppressing drug trafficking, given that around 40% of drug abuse cases in Indonesia occurred in prisons and detention centres in 2023. This study analyses the effectiveness of surveillance and law enforcement and identifies the main challenges in eradicating drug abuse. The methods used were literature review and secondary data analysis from official government reports. The findings show that manual surveillance is still prone to collusion, while the use of technology such as CCTV, electronic monitoring, and sniffer dogs can reduce smuggling by up to 25% in priority prisons. The main obstacles include budget and infrastructure limitations, especially in class II and III prisons. Inter-agency synergy has proven to increase effectiveness, with more than 150 narcotics cases uncovered throughout 2023, while a rehabilitative approach has reduced recidivism by up to 15%. This study recommends strengthening regulations, increasing human resource capacity, and integrating technology and intelligence as sustainable strategies to eradicate narcotics in prisons.